2015
DOI: 10.4236/ajor.2015.53015
|View full text |Cite
|
Sign up to set email alerts
|

Ordering and Pricing Strategies for Fresh Products with Multiple Quality Levels Considering Consumer Utility

Abstract: In this paper, considering a scenario in which there are two quality levels of fresh products and introduction of consumer utility function, we studied the optimal ordering and pricing strategies under certain quantity. Our results showed that, facing the two quality levels of fresh products, retailers would not benefit from sales of lower quality of fresh products with the deterministic demand. In the pursuit of profit maximization, the initial order quantity is smaller than the potential demand for market.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Qiao et al [35] studied a joint ordering and markdown pricing problem for perishable products with a multi-period lifetime, where stochastic demand depends on price and freshness. Moreover, some researchers proved that when the market demand is deterministic, price differentiation is not profitable for the perishable product retailers [14,15,24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Qiao et al [35] studied a joint ordering and markdown pricing problem for perishable products with a multi-period lifetime, where stochastic demand depends on price and freshness. Moreover, some researchers proved that when the market demand is deterministic, price differentiation is not profitable for the perishable product retailers [14,15,24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Retailers can also predict consumers' demand preferences for fresh food of different quality grades based on past sales experience [17,18]. In the food industry, Ma [19] established demand functions for fresh food with different quality grades based on consumers' preferences. He found that the retailer's profit is only related to the factors at the high quality level as well as ordering and preservation costs, but not to those at a low quality level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We list comparisons among our new model and those existing systems to illustrate our contribution to the academic society (Table 1). Aiello et al [20] Avinadav [34] Avinadav and Arponen [13] Avinadav et al [14] Avinadav et al [18] Avinadav et al [27] Bhuiya et al [40] Chernonog [35] Chernonog andAvinadav [31] Chuang and Lin [21] De Giovanni [9] Demirag [28] Ganguly et al [41] Gładysz et al [7] Hanukov et al [32] Hanukov et al [36] Herbon [19] Hota et al [42] Khan et al [43] Kim et al [44] Krommyda et al [37] Lee et al [3] Leśniewski and Bartoszewicz [15] Lin et al [11] Ma [22] Malik and Sarkar [10] Mishra et al [45] Muriana [23] Muriana [25] Muriana [29] Muriana [38] Orynycz et al [8] Sarkar et al [1] Sharma et al [30] Taleizadeh et al [46] Yang et al [12] Zimpel-Leal and Lettice [4] Sarkar [47] Sarkar [48] Sepehri et al [49] This study Abbreviations for the first row: S1: Sustainable; B: Backordering; L: Lean management; S2: Supply chain; P1: Pricing; S3: Shelf-life; W: Waste management; P2: Perishable.…”
Section: A Literature Review Among Modelsmentioning
confidence: 99%
“…Chuang and Lin [21] studied a two-echelon inventory model with a supplier and one retailer to decide the optimal solutions for selling price under a fixed shelf-life and a ramp type demand with shortages. Ma [22] analyzed the maximization of profit for fresh products with two quality levels by a consumer utility function to solve the optimal solutions for ordering quantity and selling price. Muriana [23] considered a food supply chain product with an uncertain shelf life that could be withdrawn and shipped to alternative destinations.…”
Section: Introductionmentioning
confidence: 99%